AB1101 Baseline Characteristics of Rheumatoid Arthritis Patients Starting Certolizumab Pegol Therapy and Glucocorticoid Prescription in the Eclair Study in 2012–2013. (9th June 2015) - Saraux, A.; Flipo, R.-M.; Fagnani, F.; Bru, I.; Cukierman, G.; Joubert, J.-M.; Czarlewski, W.; Dunkel, J.; Massol, J.; Combe, B.
Abstract : Background: In France, the ECLAIR non-interventional, multicenter study was initiated to follow up moderate to severe, active rheumatoid arthritis (RA) patients treated prospectively with CZP up to 3 years. The study is designed to provide real world evidence on RA evolution and disability progression with CZP in France. In 2003, the prescription of GCs in patients with active RA in France was evaluated and showed that >50% received GCs, although use of GCs has not been comprehensively studied to date. 1 Objectives: To describe the baseline characteristics of French RA patients starting CZP, such as disease and treatment history and concomitant medication. Methods: The ECLAIR study, run by 170 rheumatologists and 6 internal medicine specialists, was designed to be representative of the French RA population. Baseline data, provided by the treating physician or through patient questionnaires, included history of RA treatments, concomitant diseases and treatments. The current baseline analysis was of descriptive nature; no formal statistical comparison was implemented. Results: 791 patients were included: 790 used for analysis, 1 excluded due to lack of signed informed consent. Patient characteristics: mean (SD) age 55.0 (13.1) years; 78.7% female; RA duration 8.9 (9.1) years; 73.4% rheumatoid factor positive; DAS28(ESR) 4.9 (1.3); disease activity was moderate for 50.1% and high for 41.1% of patients. Mean HAQ-DI total score was 1.28 (0.69). Concomitant diseases: 23.2% (183/790) of pts had vascular disorders (mainly hypertension: 19.5%), 19.1% (151/790) metabolism and nutrition disorders (dyslipidemia: 12.0%, diabetes: 5.1%) and 17.5% (138/790) musculoskeletal and connective tissue disorders (osteoporosis: 6.2%, Sjögren's syndrome: 2.4%). Previous treatments were: NSAIDs in 54.4% (430/790) patients, steroids in 77.3% (611/790) patients, cDMARDs in 97.7% (772/790) patients (MTX: 94.1%, other DMARD: 51.8%) and bDMARDs in 31.9% (252/790) patients (anti-TNFs: 29.5%, other biologic: 12.8%). Concomitant treatments included NSAIDs in 35.2% patients, steroids in 51.4% patients and cDMARDs in 64.6% patients (MTX: 53.5%, leflunomide: 9.0%, hydroxychloroquine: 2.8%, sulfasalazine: 2.4%, azathioprine: 0.3%, thalidomide: 0.1%). Conclusions: ECLAIR is the first anti-TNF prospective real-life study conducted in France, providing insights on RA patients treated with anti-TNF therapy, such as CZP. Baseline data showed that a third of patients received CZP as monotherapy and a half of patients on CZP also received GCs, which is similar to that reported earlier in the French RA population. 1 Further targeted statistical analyses of ECLAIR data after study finalization could clarify trends associated with concomitant medication. References: Saraux A. J Rheumatol 2006;33:1258–1265. Acknowledgements: The authors acknowledge Costello Medical Consulting for editorial assistance which was funded by UCB Pharma. Disclosure of Interest: A. Saraux Consultant for: UCB Pharma, R.-M. Flipo Consultant for: UCB Pharma, F. Fagnani Consultant for: UCB Pharma, I. Bru Employee of: UCB Pharma, G. Cukierman Employee of: UCB Pharma, J.-M. Joubert Employee of: UCB Pharma, W. Czarlewski Employee of: UCB Pharma, J. Dunkel Employee of: UCB Pharma, J. Massol Consultant for: UCB Pharma, B. Combe Consultant for: UCB Pharma